Relationship between allergic diseases and mental disorders in women: A systematic review and meta-analysis - Liu, Lisha; Luo, Chao; Zhang, Mengni; Ao, Xudong; Liu, Huixia; Peng, Shunlin (Frontiers in Psychiatry, 2022)
Background: The relationship between allergic diseases (AD) and mental disorders (MD) in women has not been fully systematically evaluated, and we aimed at validating this correlation. Methods: The relevant cohort and case-control studies from the establishment of the database to February 18, 2022 in PubMed, Embase, and Cochrane library were searched by computer. The researchers conducted the quality evaluation of the included articles by reviewing and discussing with reference to relevant standards, and conducted the analysis of the correlation between female patients with AD and MD by using Review Manager 5.4. Results: Six observational studies from 2631 studies (n=1160858 women) were assessed as medium and high-quality studies. The meta-analysis demonstrated that AD was correlated with MD in female patients (OR=1.21, 95%CI: 1.14-1.29), including asthma (OR=1.16, 95%CI:1.11-1.22), allergic rhinitis (OR=1.31, 95%CI:1.06-1.63) , and atopic dermatitis in women (OR=1.37, 95%CI: 1.24-1.50) were associated with MD. At the same time, subgroup analysis was performed according to Region, Study Design, Criteria of AD and Criteria of MD, and the results demonstrated that both AD and MD were correlated in these different conditions. Conclusion: Allergic diseases in female patients do have an association with mental disorders. Systematic Review Registration: CRD42022311146 Keywords: allergic diseases, mental disorders, women, relationship, meta- analysis